Effects of Stearic Acid on Proliferation, Differentiation, Apoptosis, and Autophagy in Porcine Intestinal Epithelial Cells - Yang, Yuan; Huang, Jin; Li, Jianzhong; Yang, Huansheng; Yin, Yulong (Current Molecular Medicine, 2020)
Background: Stearic acid (SA), a saturated long-chain fatty acid consisting of 18 carbon atoms, is widely found in feed ingredients, such as corn, soybeans, and wheat. However, the roles of SA in the renewal of intestinal epithelial cells remain unclear. Methods and Results: In the present study, we found that 0.01-0.1 mM SA promoted IPEC-J2 cell differentiation and did not affect IPEC-J2 cell viability. In addition, the results showed that the viability of IPEC-J2 cells was inhibited by SA in a time- and dose-dependent manner at high concentrations. Flow cytometry and western blot analysis suggested that SA induced apoptosis, autophagy and ER stress in cells. In addition, the amounts of triglyceride were significantly increased upon challenge with SA. Moreover, the decrease in the viability of cells induced by SA could be attenuated by 4-PBA, an inhibitor of ER stress. Conclusion: In summary, SA accelerated IPEC-J2 cell differentiation at 0.01-0.1 mM. Furthermore, SA induced IPEC-J2 cell apoptosis and autophagy by causing ER stress.
Keywords: ER stress